Visual outcome in infants born to drug-misusing mothers prescribed methadone in pregnancy. Issue 2 (18th November 2013) - McGlone, Laura; Hamilton, Ruth; McCulloch, Daphne L; MacKinnon, Jane R; Bradnam, Michael; Mactier, Helen
Abstract : Background: Flash visual evoked potentials (VEPs) were abnormal in a cohort of 100 neonates exposed to maintenance methadone in utero . This prospective cohort study now describes clinical visual and electrophysiological outcomes at 6 months. Methods: Visual assessment included modified Atkinson test battery; strabismus, nystagmus, reduced visual acuity, delayed visual maturation or refractive error (>3 dioptres) defined a fail. Pattern-onset VEPs were recorded to 120′, 60′ and 15′ checks. Results: 81 drug-exposed and 26 comparison infants (79% and 52% of the original cohorts) were assessed at a median age of 27 weeks (range 26–30). 90% of drug-exposed infants had been additionally exposed to illicit drugs and 41% to excess alcohol in utero. 40% of the drug-exposed cohort failed clinical visual assessment: the relative risk of abnormal assessment was 5.1 (95% CI 1.3 to 20; p=0.02). Nystagmus was particularly common. VEP peak times were slower and amplitudes smaller in drug-exposed infants, of whom 70% had one or more abnormal VEP parameter. Abnormal visual outcome at 6 months was not associated with the pattern of additional drug exposure or a history of neonatal abstinence. Conclusions: Abnormal visual electrophysiology in infants born to drug-misusing mothers prescribed maintenance methadone persists to 6 months of age, and is associated with abnormal clinical visual assessment.